POLA ASUH ANAK PADA PASANGAN PERNIKAHAN DINI PERSPEKTIF HUKUM ISLAM (Studi Kasus di Desa Sumbermulyo Kecamatan Jogoroto Kabupaten Jombang Provinsi Jawa Timur) - Ahmad Rizky Hidayat; Habibi Al Amin (Kampus Akademik Publiser, 2024)
Considering that parenting patterns are so important for children's development, it is necessary to conduct research on the application of parenting patterns, so here the researcher took the object in Sumbermulyo Village, where parents who married early did not seem ready to care for children, so they provided full care to them. his grandmother. In fact, it is not necessarily the case that the care provided by the grandmother is in accordance with the needs of today's children, especially since it is also found that parents easily give gadget freedom to their children, which then results in the child becoming addicted and cognitively declining. So the process of parenting children in the family must be supported by attention and encouragement from both parents.The type of research the author uses is qualitative, applying a qualitative descriptive approach. The data collection methods used are interviews, observation, documentation. And the data is analyzed by reducing the data, explaining the data, and drawing conclusions.The results of this research show that in practice, early married couples apply 2 parenting patterns for their children, such as a democratic parenting pattern and a permissive parenting pattern, which, if seen from the principles of hadlonah, they have indeed fulfilled, such as looking after, protecting, nurturing and caring for the child from the womb until the moment. This, and it has been fulfilled that he gives custody to his grandmother, but this has an impact on parents who apply a permissive parenting style to their children because implementing a permissive parenting pattern has the potential to make children unsupervised in their social interactions.